The Impacts of Multi-blockholder Contestability and Coalition on the Risk of Korean Companies - Kim, Hung Sik; Cho, Kyung-Shick (Asian Academy of Management Journal of Accounting and Finance, 2022)
We examine the relationship between multi-blockholder contestability and coalition and firm risk using an unbalanced panel of 646 Korean non-financial firms with 7,582 firm-years from 2010 to 2017 (8 years). For multi-blockholder contestability, we use the second-to-first blockholder contestability index and the second-and third-to-first blockholder contestability index. The Herfindahl-Harshman Index Concentration and Herfindahl-Harshman Index Difference are used for a multi-blockholder coalition. Using different measures of contestability, we show that contestability among multiple blockholders is negatively related to beta. It is also shown that the probability (variance) of forming a dominant coalition among multiple blockholders is negatively related to beta. This suggests that contestability and the probability of forming a dominant coalition among multiple blockholders reduce corporate risk. This study expands on the existing literature on the relationship between corporate risk and ownership. This study shows that the multi-blockholder contestability and coalition may be one factor determining the risk of a company. Our findings will contribute to policymakers and investors who are interested in the relationship between corporate risk and blockholder contestability and dispersion in the Korean stock market.